2012
DOI: 10.3892/mmr.2012.1036
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17, produced by lymphocytes, promotes tumor growth and angiogenesis in a mouse model of breast cancer

Abstract: Previous studies have suggested that interleukin-17 (IL-17), an inflammatory cytokine expressed predominantly by Th17 cells, is highly expressed in tumor tissue and may help tumors to evade immune surveillance. In this study, the significance of IL-17 expression in the tumors of murine models of breast cancer was explored. BALB/c mice were injected with MA782/5S28102 or 4T1 breast cancer cell lines to establish breast tumors. The expression of IL-17 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 16 publications
2
63
0
1
Order By: Relevance
“…It has also been reported that the prevalence of Th17 cells, as well as ROR␥t expression are diminished among PBMCs of the patients with NSCLC [19,38]. Contrary to these findings, other investigations suggested that Th17 cells may induce angiogenesis and participate in pro-tumorigenic processes associated with tumor growth [41][42][43][44]. Consistently some studies indicated that the percentage of these cells is increased in the peripheral blood of the patients with uterine cervical cancer (UCC), HNSCC and pancreatic cancer [24,45,46].…”
Section: Discussionmentioning
confidence: 87%
“…It has also been reported that the prevalence of Th17 cells, as well as ROR␥t expression are diminished among PBMCs of the patients with NSCLC [19,38]. Contrary to these findings, other investigations suggested that Th17 cells may induce angiogenesis and participate in pro-tumorigenic processes associated with tumor growth [41][42][43][44]. Consistently some studies indicated that the percentage of these cells is increased in the peripheral blood of the patients with uterine cervical cancer (UCC), HNSCC and pancreatic cancer [24,45,46].…”
Section: Discussionmentioning
confidence: 87%
“…In this Moreover, various T cell subsets have been implicated in angiogenesis, including Tregs correlation with MVD in other malignancies such as endometrial and breast carcinoma [20,21] and Th17 through infusion of IL-17 in mouse models of breast carcinoma, which may accelerate the progression of tumors by promoting angiogenesis [22]. Tregs may contribute to tumor angiogenesis both indirectly and directly by suppressing Th1 effector T cells that release angiostatic cytokines like TNF-a and interferon gamma (IFN-c) and by releasing high levels of vascular endothelial growth factor (VEGF), which promote capillary tube formation in vitro, respectively [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, other reports have suggested potent protumor functions for IL-17A and IL-17A-producing cells. IL-17A overexpression in tumor cell lines promotes angiogenesis and tumor growth in immunodeficient mice (10), and IL-17A can promote tumor growth by enhancing angiogenesis in immunocompetent hosts (11). IL-17A can induce IL-6 production, which in turn promotes tumor growth in a Stat-3-dependent pathway (12).…”
Section: Introductionmentioning
confidence: 99%